Alexandra Eppinger. Hercules in der Spätantike. Die Rolle des Heros im Spannungsfeld von Heidentum und Christentum - Vos, Gary (Journal of Greek Archaeology, 2017)
In this revised thesis by Alexandra Eppinger (hereafter ‘E.’), defended at the University of Heidelberg in 2013, the ubiquity of Heracles/Hercules in the art, archaeology, and literature of ‘the long late antiquity’ (defined as c. 250-600 AD) is ascribed to a desire by individuals or communities – be they pagan or not – to come across as ‘learned’, to show off their status, and/or to have something to talk about. At the same time the book attempts to chart how Christians and non-Christians reacted to Hercules (as I shall call him in the remainder of this review). It must be said at the outset that the value of E.’s book lies in the synthesis of a great variety of source-material that allows us to see the late-antique reception of Hercules in action, as it were, even if the presentation of the material sometimes hampers her argument and leads to occasional repetitions that easily could have been avoided. Undoubtedly, this is partly due to the ambitious goal of cataloguing reactions to Hercules in such a diverse and dynamic period and the occasional wavering between the two objectives that the book has set itself. Despite this, Hercules in der Spätantike does many things well.